Analisis Keterkaitan Sektor Industri Manufaktur Besar dan Sedang di Provinsi Jawa Timur dengan Menggunakan Tabel Input-Output - Betty Silvia Ayu Utami (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
The purpose of this research is to know and analyze the role and backward linkage and forward linkage of big and medium manufacturing industry in East Java Province. The data used in this study is cross section data, data to measure the linkage of economic sector. While the population of this research is all economic sector in East Java Province, which is divided into 66 economic sectors in accordance with Input-Output analysis (I-O). From the analysis result, it is concluded that the backward linkage condition shows the bamboo, wood and rattan industry sub sector, the non-metallic minerals sub industry, and the cement sub-industry has the greatest value, while from the forward linkage shows that the petroleum refinery industry sub sector, sub industry of goods.